2006
DOI: 10.1179/146532806x152827
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of the practice of genital mutilation of girls in Khartoum, Sudan

Abstract: FGM is still practised widely in Khartoum and probably in many parts of northern Sudan and the type undertaken is often the most severe. Parental education, socio-economic level and religion are important determinants of the practice, but social pressure on parents and girls seems to play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 15 publications
6
38
2
Order By: Relevance
“…24 This was in agreement with who have suggested that rural women are more likely to be mutilated than an urban one. That could be explained by cultural believes and low educational level were more prevalent in rural areas.…”
Section: -21supporting
confidence: 81%
See 1 more Smart Citation
“…24 This was in agreement with who have suggested that rural women are more likely to be mutilated than an urban one. That could be explained by cultural believes and low educational level were more prevalent in rural areas.…”
Section: -21supporting
confidence: 81%
“…16,20 The current study was in line with a study conducted in Sudan; it reported that the majority of FGM occurred at home and practiced by birth attendant. 24 The findings bear similarities to the results of Ethiopia study that FGM complications included pain, bleeding, and infection. 17 The current study reported that mutilation had adverse effect on female sexual function as desire, arousal, orgasm, and sexual satisfaction; it also clarified the high percentage of sexual dysfunction among mutilated women that is in agreement with results of a study conducted in Gambia, review study, African countries …”
Section: -21supporting
confidence: 63%
“…According to data reported by WHO, prevalence of FGM in Sudan was 89% and types performed were type I (15%), type II (3%), type III (82%). In Somalia, the prevalence of FGM was 100% and type III was the only type performed [16]. According to the types of FGM in this study, the most common types were type I (49.2%) and type II (50.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps most worrying is the apparent trend toward the practice being carried out by trained health personnel, as opposed to traditional circumcisers. Surveys in some countries indicate that at least one-third of women whose daughters underwent FGM had the procedure carried out by a trained health professional [10]. And a comparative analysis of Demographic and Health Surveys shows a very clear and sometimes substantial increase in the medicalization of FGM in some countries [11].…”
Section: Prevalence and Consequences Of Fgmmentioning
confidence: 99%